Analisis Kepuasan Kerja Pegawai Pada Kantor Dinas Sosial Kota Bima - Fitri Fadinha Mapasere Fitri; Jaenab Jaenab (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2022)
This study aims to determine the analysis of employee job satisfaction at the Bima City Social Service Office. This study uses a descriptive type of research with a qualitative approach. For sampling, a technique (purposive sampling) was used by determining the sample as respondents were all 32 state civil servants (ASN) at the Bima City Social Service office. employee job satisfaction at the Social Service Office with a tcount of -63.985, so the decision was taken that Ha was accepted, while the significance level was 0.000 which stated that Ho was rejected.